2019
DOI: 10.1016/j.ijms.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of acetonitrile

Abstract: The ionization of acetonitrile has been studied using both electron and photon ionization combined with coincidence detection techniques. Relative partial ionization cross sections and relative precursor-specific partial ionization cross-sections are determined for all the cations formed from single, double and triple electron ionization of CH3CN from 30-200 eV electron energy. These cross sections characterize, distinguish and quantify the positive ions formed from these levels of ionization over the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 60 publications
(82 reference statements)
1
16
0
Order By: Relevance
“…Using this methodology the value of f for the experiments involved in this study was found to be 0.25, a value in accord with previous determinations for our apparatus. 48 An example of the relationship between the detected ion intensities in the singles mass spectra I[X + ] and the detection efficiency f is shown by eqn (1), where N n is the number of X + ions formed via ionising events involving the loss of n electrons from a PF 3 molecule. Similar equations can be constructed for pairs and triples P 2 [X + ], P 3 [X + ], T[X + ], as shown in the literature.…”
Section: Data Reduction: Coincidence Tof-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this methodology the value of f for the experiments involved in this study was found to be 0.25, a value in accord with previous determinations for our apparatus. 48 An example of the relationship between the detected ion intensities in the singles mass spectra I[X + ] and the detection efficiency f is shown by eqn (1), where N n is the number of X + ions formed via ionising events involving the loss of n electrons from a PF 3 molecule. Similar equations can be constructed for pairs and triples P 2 [X + ], P 3 [X + ], T[X + ], as shown in the literature.…”
Section: Data Reduction: Coincidence Tof-msmentioning
confidence: 99%
“…The derivation of the above equations, and the other related equations for this analysis, have been described in detail in the literature. 33,48 It is possible to determine the kinetic energy release (KER) of each dicationic dissociation reaction detected in the pairs spectrum. This determination is performed by generating a TOF difference spectrum for the dissociation of interest, a histogram of intensity against (t B À t A ) as discussed above.…”
Section: Data Reduction: Coincidence Tof-msmentioning
confidence: 99%
“…The main product of the CH 3 CN photolysis is HCN molecules. Their preferable formation according to the path CH 3 CN→ CH + H + HCN was previously observed under the action of UV light [23], electron beam [20], and photon beam [22]. The HCN concentration after the first stage of the irradiation for 2 s is ~64% for CH 3 CN@CF 0.5 and ~57% for CH 3 CN@CF 0.3 , and it reduces to ~49% for CH 3 CN@CF 0.5 and ~47% for CH 3 CN@CF 0.3 after the 200-s exposure.…”
Section: Discussionmentioning
confidence: 84%
“…This molecule contains an element (nitrogen) that is absent in CF x and therefore is a convenient probe for studying host-guest interactions under illumination. Photolysis of acetonitrile attracts attention because these molecules are present in interstellar medium [20] and understanding of the acetonitrile fragmentation by ionizing radiation can shed light on the early stages of stars formation [21]. A study of the photolysis of gaseous acetonitrile using synchrotron radiation (SR) in the 7-22 eV range revealed the formation of CN and CH species [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation